Colonial Discourse and Resistance in the Novel Perawan Desa by W.R. Supratman - Widyanuari Eko Putra; Nurdien Harry Kistanto; M. Suryadi (Balai Bahasa Kalimantan Tengah, 2023)
W.R. Supratman wrote the novel Perawan Desa (1929) in the colonial era. The novel tells the life of colonial society in the Dutch East Indies era. This study examines the colonial discourse and resistance in the novel with a postcolonial approach. The colonial discourse in question is discrimination, racial superiority, and racism. Forms of resistance in question are stereotype, mimicry, ambivalence, and hybridity. The method used is descriptive qualitative. As a result, the novel contains colonial discourses and resistance. Acts of racial superiority and racism are shown in scenes of harsh treatment of natives, and different treatment before the law. The mimicry is shown in the imitation of the way of dressing, attitude, and reading habits of Dutch novels. The negative assumptions about other parties outside the group show the stereotype is shown in the negative assumptions about other parties outside the group. The ambivalence is shown in the indigenous interest in Dutch newspapers and the Dutch dislike of working as government employees. Hybridity is shown in the embodiment of Dutch houses decorated with local ornaments and the nickname